2019
DOI: 10.1111/ajco.13241
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world outcome with abiraterone acetate plus prednisone in Asian men with metastatic castrate‐resistant prostate cancer: The Singapore experience

Abstract: Introduction: Several small studies have reviewed the efficacy of abiraterone acetate plus prednisolone (AAP) in clinical practice outside a trial setting. We report the largest cohort study of clinical outcomes in metastatic castrate-resistant prostate cancer (mCRPC) patients treated with AAP in a multicenter multiracial clinical setting. Methods:A retrospective analysis on mCRPC patients treated at four tertiary hospitals in Singapore from 2012 to 2017 was conducted. Disease characteristics, treatment outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…The favorable results of first-line abiraterone in men with mCRPC emerged in previous relatively small retrospective real-life investigations 26 , 27 , 28 , 29 , 30 are here confirmed in a prospective large study with long follow-up.…”
Section: Discussionsupporting
confidence: 79%
“…The favorable results of first-line abiraterone in men with mCRPC emerged in previous relatively small retrospective real-life investigations 26 , 27 , 28 , 29 , 30 are here confirmed in a prospective large study with long follow-up.…”
Section: Discussionsupporting
confidence: 79%
“…This can have impact on survival outcomes. A subset analysis in Chan et al of chemotherapy naive patients with an ECOG 2-4 showed a poorer OS and PFS (12). Similarly, Boegemann et al (15), also showed that poorer ECOG was associated with shorter time to treatment failure.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, similar to our study, real world studies on abiraterone in mCRPC have showed poorer outcomes than in the COU trials. A Singaporean retrospective audit (12) looking at abiraterone in the real world mCRPC population of 200 patients demonstrated a median OS of 20 months for men who were chemotherapy naïve and only 11.3 months for men who have had prior chemotherapy. The variability in patient population in terms of ECOG performance status and comorbidities in the real world are important factors to consider given the majority of patients with prostate cancer are elderly often with multiple medical problems.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-seven were removed as duplicates due to overlapping among databases. After screening the titles and abstracts and then the full texts, 27 publications 17 43 were shortlisted. No additional studies were identified from the bibliographic search.…”
Section: Resultsmentioning
confidence: 99%
“…One RCT 26 and four real-world studies 29 33 contributed evidence for AAP in patients with mCRPC. In the RCT, Ye et al .…”
Section: Resultsmentioning
confidence: 99%